EFFECTS OF WORK EXPECTATION AND ACHIEVEMENT MOTIVATION ON PERFORMANC EEFFICIENCY OF EMPLOYEES IN COSMETICS MANUFACTURING COMPANIES IN BANGKOK - ศรีไกร, ปริศนา (Pathumthani University Academic Journal, 2021)
The objectives of this independent study were: 1) personal factors and performance efficiency of employees in cosmetics manufacturing companies, 2) expectations of work and performance efficiency of employees in cosmetics manufacturing companies, and 3) achievement motivation and performance efficiency of employees in cosmetics manufacturing companies. The sample group used in this study comprised 250 staffs employed by cosmetics manufacturing companies in Bangkok. The instrument used to collect data was a questionnaire. The statistics used to analyze data were percentage, mean, standard deviation, independent sample t-test, one-way ANOVA and multiple regression analysis. The study results Work expectations and achievement motivation affect work efficiency. Overall, it's at a high level. When considering each aspect, it was found that work expectations Security at work Relationship with supervisors And the relationship with colleagues affects the efficiency of the employees of cosmetic manufacturing companies and found that, it was found that achievement motivation, in terms of the need for achievement, the need for affiliation, and the need for power, demonstrated statistically significant effects on performance efficiency of staff employed by cosmetics manufacturing companies in Bangkok at a level of .05.